Evaluation of the Chemical Composition of Brazilian Commercial Cymbopogon citratus (D.C.) Stapf Samples - Evandro de Castro Melo; RÃƒÂ³bson Ricardo Teixeira; CÃƒÂ©lia Regina ÃƒÂlvares Maltha; Ana Paula Martinazzo; Ulisses Alves Pereira; Luiz ClÃƒÂ¡udio Almeida Barbosa (Molecules, 2008)
Abstract: The concentration and the chemical composition of the essential oils obtained from different samples of Cymbopogon citratus were evaluated. Among the 12 samples investigated (11 dried leaf samples and fresh plant leaves), seven presented essential oil concentrations within the threshold established by the Brazilian legislation. The moisture content was also determined and the majority of the samples presented humidity contents near 12%. The GC and GC/MS analyses of the essential oils led to identification of 22 compounds, with neral and geranial as the two major components. The total percentage of these two compounds varied within the investigated sample oils from 40.7% to 75.4%. In addition, a considerable variation in the chemical composition of the analyzed samples was observed. The process of grinding the leaves significantly decreased (by up to 68%) the essential oil content, as well as the percentage of myrcene in the oils.